PENGARUH GAYA KEPEMIMPINAN, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN. ( Studi pada KUD Gondanglegi) - Dasri Mauliddinar Pertiwi; Muhammad Mansur; Afi Rachmat Slamet (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
ABSTRACT The aim of this study was to know the influence of leadership style, motivation and discipline of work toward the employee performance of KUD Gondanglegi. The subject of the study was from the employee of KUD Gondanglegi that consists of 50 respondents. The method of collecting data in this study used census method, also statistical analysis and multiple linear regression analysis are used in this study.Based on the result of multiple linear regression analysis can be known that leadership style was 0,109, motivation was 0,240 and discipline of work was 0,347. It meant that leadership style was significant effect toward the employee performance of KUD Gondanglegi, motivation was significant effect toward the employee performance of KUD Gondanglegi, discipline of work was significant effect toward the employee performance of KUD Gondanglegi, leadership style, motivation, and discipline of work influenced simultaneously toward the employee performance of KUD Gondanglegi. Key words: leadership style, motivation, discipline of work and the employee performance